A study on noninvasive ventilation in Type-II respiratory failure in a tertiary care center - Roopa Suresh; Sanjay Reddy; Y Rajasekher Naidu; Y J Visweswara Reddy; P E Dhananjaya; A Jaganath (APIK Journal of Internal Medicine, 2022)
Background: Type II respiratory failure is a common complication with considerable morbidity and mortality. Noninvasive ventilation (NIV) has been used preferentially with better results. The objective of this study was to assess the outcome and complications of NIV in type II respiratory failure patients. Methods: A clinical observational study of 67 consecutive adult patients with Type II respiratory failure who were assigned NIV, fulfilling inclusion and exclusion criteria were recruited in the study. NIV Bi level positive airway Pressure (Bi PAP) (spontaneous mode) was used in all patients with settings of 12/6 initially. Based on arterial blood gas values and clinical status, settings were adjusted and followed up as per British Thoracic Society guidelines (2016). In case of worsening of mental status, deterioration of potential of hydrogen (PH), increased partial pressure of carbon dioxide, and intolerance to NIV, patients were subjected to invasive ventilation within the first 4 h of NIV initiation. Results: Patients diagnosed with acute exacerbation of chronic obstructive pulmonary disease (–92.5%), and cases of obstructive sleep apnea (7.5%), showed significant improvement in NIV trial over 24 h in 91.7% and 100%, respectively, by the way of reduction of PCO2 levels and improvement in partial pressure of oxygen, oxygen saturation, which was statistically significant in 89.5% of patients. Clinical improvement noted by the decrease in heart rate, respiratory rate was also statistically significant with a P < 001. However, PH did not show significant changes in our study. Conclusions: A trial of NIV is a useful alternative to mechanical ventilation in many different situations with Type II respiratory failure. Advantages of cost-effectiveness, minimal utilization of intensive care unit resources, low morbidity and mortality rates with patient-friendly equipment features contribute to its preference over invasive ventilation.